Penguatan Literasi Dasar sebagai Jembatan Generasi Emas NTT - Koroh, Lanny Isabela Dwisyahri; Nalle, Derlin Novita (Devotion: Jurnal Pengabdian Masyarakat, 2024)
Scientific backwardness is the result of a lack of interest in developing basic literacy during education. This problem occurs due to the lack of facilities that support the development of basic literacy, especially reading, namely the lack of reading books in elementary schools. Apart from that, in carrying out the learning process teachers are also not creative in creating a pleasant learning atmosphere. A problem that is still widespread in the world of elementary school education is that there are still elementary school students who cannot read. Therefore, the current aim of Community Service is to develop basic literacy, especially reading. It is necessary to carry out several supporting activities that can increase motivation and interest in learning in elementary school students. The development method used is by sharing picture learning books written in two languages, carrying out reading exercises for elementary school students and holding reading competitions by giving awards to each competition participant to foster students' interest in learning. The results of community service found were that teachers and students realized that basic literacy in elementary school education was very necessary because with good literacy development, teachers and students would be able to face various developments in current globalization. The form of literacy development carried out aims to bridge elementary school students and teachers to face various challenges that will arise in the future golden generation.